Implementasi Gerakan Sekolah Menyenangkan Dalam Peningkatan Sikap Religius Siswa SMKN 1 Portibi Kabupaten Padang Lawas Utara - Pondang Suriadi Siregar; Syafnan Syafnan; Muhammad Roihan Daulay (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas (STIT PL) Gunung Tua, 2025)
The phenomenon of declining moral values and religious attitudes among students—such as a lack of courtesy, increased violence, and low empathy—has become a serious concern in the field of education. To address this issue, one approach that has been implemented is the Joyful School Movement (Gerakan Sekolah Menyenangkan, or GSM). GSM aims to create a friendly and enjoyable learning environment that supports the development of positive character traits, including students’ religious attitudes. This study employed a qualitative method with a phenomenological approach. Data were collected through interviews, observations, and documentation, focusing on the direct experiences of students, teachers, and school principals in implementing GSM. The findings indicate that GSM is carried out through humanistic learning, regular religious activities such as group prayers and discussions, the use of religious visual media, and the involvement of student religious organizations (ROHIS). The positive impacts include increased student participation in religious activities, greater awareness of worship practices, and the emergence of polite, disciplined, and responsible behavior. The success of GSM is supported by the school’s commitment, the availability of facilities, and parental involvement. However, challenges remain, such as the low awareness among some students, a shortage of religious mentors, external environmental influences, and limited time.